(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Since the establishment, the University of Kufa has required to prepare specialized staff capable of serving the community and preparing for the planning of future specializations, in addition to establishing and investing in joint cooperation relations between the university and government departments, and this is one of the essential functions and obligations by providing these consultations to solve the technical and scientific problems that society needs. Nowadays, the scientific and practical academic method has become the basis for effective and organized leadership in cognitive development, solving societal problems, and employing scientific research in the aspects of the Iraqi government in general and Najaf Al-Ashraf governorate in particular.